2006
DOI: 10.1097/01.aog.0000218705.87329.4a
|View full text |Cite
|
Sign up to set email alerts
|

Rate of Pathology From Atypical Glandular Cell Pap Tests Classified by the Bethesda 2001 Nomenclature

Abstract: II-2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
41
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 21 publications
11
41
3
Order By: Relevance
“…However, such a policy could lead to overtreatment, with its surgical and reproductive morbidities, especially in young women. Moreover, BNCs in women over 35 years are more likely to be endometrial in origin, that is, hyperplasias and carcinomas (DeSimone et al , 2006). In our study, 24% of over 35s compared to 49% of under 35s had high-grade histology.…”
Section: Discussionmentioning
confidence: 99%
“…However, such a policy could lead to overtreatment, with its surgical and reproductive morbidities, especially in young women. Moreover, BNCs in women over 35 years are more likely to be endometrial in origin, that is, hyperplasias and carcinomas (DeSimone et al , 2006). In our study, 24% of over 35s compared to 49% of under 35s had high-grade histology.…”
Section: Discussionmentioning
confidence: 99%
“…21 Approximately 50% of women with AGC on routine screening will have no underlying pathology on subsequent sampling. [14][15][16] Multiple studies have examined the role of HPV testing in the triage of AGC. [17][18][19][20]22 A recent study demonstrated that AGC lesions testing positive for HR-HPV by Hybrid Capture 2 (Digene corp) DNA probe are more likely to represent HSIL rather than AIS on follow-up compared to those that are negative for HPV.…”
Section: Discussionmentioning
confidence: 99%
“…Additional endometrial sampling is recommended in women 35 years of age or older, and in women at risk of endometrial neoplasia. In the literature, the incidence of significant lesion in women with AGC-NOS varies from 5% to 33% (Haidopoulos et al, 2005;DeSimone et al, 2006;Behtash et al, 2007;Westin et al, 2008;Adhya et al, 2009;Schnatz et al, 2009;Zhao et al, 2009) as compared with 41%-70% in women with AGC-FN smears (Haidopoulos et al, 2005;DeSimone et al, 2006;Westin et al, 2008;Adhya et al, 2009;Schnatz et al, 2009). Extragenital malignant lesions were found in less than 1% of women with AGC cytology (Zhao et al, 2009).…”
Section: Atypical Glandular Cellsmentioning
confidence: 99%